Software Greenability: A Case Study of Cloud-Based Business Applications Provisioning - Acar, H.; Benfenatki, H.; Gelas, J.-P.; Ferreira da Silva, C.; Alptekin, G. I.; Benharkat, A.-N.; Ghodous, P. (CLOUD 2018 - IEEE 11th International Conference on Cloud Computing, 2018)
The emission of CO2 due to ICT (Information and Communication Technologies) is found as equivalent to aviation sector. Although the energy consumption in ICT is due both to hardware and software. In recent decade, the energy efficiency studies focus on the hardware part, especially with the development of cloud computing. Indeed, it is the software application that is responsible for executing tasks, that indirectly affects the hardware energy consumption. This work focus on software energy consumption. We introduce a methodology which evaluates and improves the software greenability by considering its energy consumption, performance and readability. Contrary to existing methodologies, we associate the effect of several components (CPU, memory, disk and network) when estimating software energy consumption instead of considering only the CPU as it is the case in literature. Moreover, the proposed framework can dynamically examine source code to integrate some measurement functionality. A Tool to Estimate Energy Consumption (TEEC) is implemented and its applicability is demonstrated on the case of cloud-based business application provisioning software, called MADONA. MADONA allows dy- namically generating service-oriented business applications by automatically composing business services and automatically deploying the generated applications on cloud environment.